Myo-inositol affects the health, metabolome, and lactation performance of peripartum dairy cows - Wang, Chun-zheng; Dong, Jia-nan; Sun, Wu-wen; Qu, Ke; Lin, Zi-chen; Aschalew, Natnael D.; Zhao, Yang; Sun, Zhe; Ta, Na; Zhao, Zhi-kun; Liu, Yong-jun; Zhang, Wei-gang; et al. (Frontiers in Immunology, 2025)
IntroductionYeast culture (YC) has become a crucial microecological preparation for regulating the ruminal environment and improving ruminant health. Myo-inositol is an effective substance in YC, our study aimed to investigate whether myo-inositol can regulate metabolism and influence the health of dairy cows. Therefore, this study explored the effects of myo-inositol on the health, metabolome, and lactation performance of peripartum dairy cows using both in vitro and in vivo models.MethodsThe ANKOM RFS gas production system was used for the in vitro experiment; Twenty four healthy Holstein cows were assigned to CON group (n = 4; no supplementation of YC or myo-inositol), YC group (n = 10; 2 g/kg YC), and IN65 group (n = 10; 2 g/kg YC + 16 mg/kg myo-inositol) for in vivo experiment.ResultsThe concentrations of five volatile fatty acids (acetic acid, butyric acid, isobutyric acid, valeric acid, and isovaleric acid), and total volatile fatty acids were significantly higher in the IN65 group compared to the CON group at 6 h in vitro (P < 0.01). Therefore, 2 g/kg YC plus 16 mg/kg myo-inositol was selected for in vivo experiment. It was found that the average milk production of the IN65 group increased by 4.00% and 4.05% respectively, compared to the control group and YC group on day 21 postpartum. The levels of superoxide dismutase (SOD), total antioxidant status (TAS), and total oxidative status (TOS) were significantly higher on day 21 compared to day 1 postpartum (P < 0.01). However, a trend indicating a decrease in immune function was observed in the IN65 group compared to the CON group. These findings suggested that myo-inositol may improve the health of postpartum dairy cows. Additionally, Mantel analysis showed acetic acid was positively correlated with D-glyceric acid and xanthosine. Similarly, D-glyceric acid, inosine 5-monophosphate, and xanthosine were positively correlated with microbiota at the genus, such as Bulleidia and Moryella.DiscussionIn summary, myo-inositol influences energy metabolism by modulating rumen microbial abundance, improving dairy cow health, and increasing milk production.